The Reception of Vatican II in Systematic Theology - Murray, Paul D. (Oxford University Press, 2023)
This chapter does three things. First, it treats of the divergent theological receptions of Vatican II with a view to the challenges which this presents for contemporary Catholic theology and life. Second, it indicates something of the range of ways in which Catholic theologians have sought to resolve some of the ecclesiological matters opened up by the Council’s documents. Third, it offers judgment on how these same issues might best be taken forward in Catholic systematic theology and Catholic life in a manner capable of serving whole-church Catholic flourishing. The aim is both to comment on what has been and to indicate what might be, and so contribute to the continuing story of Catholicism’s reception of Vatican II and the role of systematic theology in that process.
EPrint Processing Status: Full text deposited in DRO, closed access